Feasibility Analysis of Injection Molding Machine Replacement at CV Gradient - Kusmiaty, Agnest Mela Dwi; Pratama, Oktioza; Apfiasari, Steela; Rudini, Rezki (Journal of Industrial Engineering & Management Research, 2026)
The motorcycle industry in Indonesia continues to show strong market potential.Based on data from the Asosiasi Industri Sepeda Motor Indonesia (AISI), motorcycleproduction between 2013 and 2017 remained high despite a temporary decline in 2015. The increasing demand for motorcycles has directly impacted the demand for spare parts, including Spring Guide components produced by CV Gradient. CV Gradient, a Bandung- based spare parts manufacturer established in 1993, supplies products to major industrial clients. However, the company faces significant production gaps due to limited machine capacity and frequent breakdowns of its Injection Molding machine. Although annual demand for Spring Guide HKWB ranges from 1.12 to 1.30 million units, actual production remains fixed at 806,400 units per year, resulting in an average production gap of 33%. Machine downtime averages 12 days per month (144 days per year), reducing machine utilization toonly 50%. As a result, unmet demand must be subcontracted, leading to lower profit margins, higher costs, and potential quality and delivery risks. Financial comparison shows that full in- house production would generate approximately IDR 40–50 million higher annual profit compared to partial subcontracting. This indicates a significant opportunity loss due to current production inefficiencies. Based on operational and financial considerations, replacing the existing Injection Molding machine is economically feasible. The investment would reduce downtime, increase production capacity, improve quality control, minimize subcontractingdependence, and enhance profitability. Given that the company currently serves only 12% of national demand, machine replacement also supports long-term growth and competitiveness.